2009
DOI: 10.1002/bem.20484
|View full text |Cite
|
Sign up to set email alerts
|

Radiation from mobile phone systems: Is it perceived as a threat to people's health?

Abstract: The aim of this study was to explore the prevalence, nature and determinants of concerns about mobile phone radiation. We used data from a 2006 telephone survey of 1004 people aged 15+ years in Denmark. Twenty-eight percent of the respondents were concerned about exposure to mobile phone radiation; radiation from masts was of concern to about 15%. In contrast, 82% were concerned about pollution. Nearly half of the respondents considered the mortality risk of 3G phones and masts to be of the same order of magni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…This suggests that, in the Bangladeshi population surveyed, risk perceptions are primarily driven by perceptions of crime and annoyances, such as "teasing" and handset theft, rather than risks to health. As has been the case in other studies, risk perceptions associated with mobile phone use are higher among women than men, (8,27) an observation that aligns with the international risk perception literature in general. (50) Chen and Katz (51) argue that early studies of the adoption of mobile phone technology in developed countries showed that safety and accessibility were the primary reasons why people adopted the new technology, reflecting what might be described as its instrumental function.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This suggests that, in the Bangladeshi population surveyed, risk perceptions are primarily driven by perceptions of crime and annoyances, such as "teasing" and handset theft, rather than risks to health. As has been the case in other studies, risk perceptions associated with mobile phone use are higher among women than men, (8,27) an observation that aligns with the international risk perception literature in general. (50) Chen and Katz (51) argue that early studies of the adoption of mobile phone technology in developed countries showed that safety and accessibility were the primary reasons why people adopted the new technology, reflecting what might be described as its instrumental function.…”
Section: Discussionsupporting
confidence: 85%
“…(2,3) However, research into the risk perception of citizens in developed countries has indicated that many people have health concerns with regard to the use of both handsets and base stations. (4,5) To date, research focused on citizens' risk and benefit perceptions associated with mobile technology has primarily been conducted in developed countries, such as Austria, (6) Spain, (7) Denmark, (8) Australia, (9) France, (10) and the United Kingdom. (11,12) Due to cultural and economic differences, the extrapolation of the results of these studies in the developing world may not be straightforward, as little is understood about cultural preferences and perceptions associated with mobile communication technology.…”
Section: Introductionmentioning
confidence: 99%
“…4 Risk perception studies show that some communities, members of the general public, academics and politicians have concerns about possible health effects of exposure to radiofrequency (RF) energy transmitted by mobile phones and wireless networks. 5 …”
Section: Introductionmentioning
confidence: 99%
“…This is particularly true in urban areas, where these antennas are being deployed on rooftops, facades, high masts or even indoors. At the same time, a general public concern about possible health hazards caused by radiation from these systems has emerged in the last several years [Frick et al, 2002;Kristiansen et al, 2009]. In spite of the existence of limits to the allowed population exposure, there exist many examples of residents that oppose the installation of new antennas close to their buildings.…”
Section: Introductionmentioning
confidence: 99%